1994
DOI: 10.1139/v94-056
|View full text |Cite
|
Sign up to set email alerts
|

Apparent molar heat capacities and volumes of some aqueous solutions of aliphatic amino acids at 288.15, 298.15, 313.15, and 328.15 K

Abstract: 362 (1994).The thermodynamics of amino acid systems are key to the understanding of protein chemistry. We have found that many previous studies of the apparent molar volumes and heat capacities of aqueous solutions of amino acids were conducted at the standard temperature of 298.15 K. This does not allow for the fact that most biological processes occur at temperatures removed from this standard condition.In an attempt to address this imbalance we have measured densities and heat capacities for aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 16 publications
12
89
1
Order By: Relevance
“…The weights used in these calculations were calculated as the reciprocals of the squares of the uncertainties in the apparent molar volumes and heat capacities (1,17). Calculated uncertainties are contained in parentheses in Tables 1-6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weights used in these calculations were calculated as the reciprocals of the squares of the uncertainties in the apparent molar volumes and heat capacities (1,17). Calculated uncertainties are contained in parentheses in Tables 1-6.…”
Section: Resultsmentioning
confidence: 99%
“…chemical properties of aqueous amino acid systems that we are constructing (1)(2)(3). This data base provides the framework on which we have constructed group additivity analyses that allow for the estimation of standard state volume and heat capacity data for aqueous amino acid and peptide systems in the temperature range 288.15-328.15 K. More specifically, the data reported in this paper allow for the calculation of the temperature dependences of peptide group contributions to structural components of standard state volumes and heat capacities.…”
Section: Group Additivity Analysesmentioning
confidence: 99%
“…In an aqueous solution, a DMSO molecule preferentially combines with two water molecules and forms a composite molecule as follows (13) (CH 3 ) 2 S = O OH 2 H O H Kinetic data from nuclear magnetic resonance and infrared techniques have shown that the interaction due to hydrogen bonding between DMSO and H 2 O is stronger than that between H 2 O molecules. Because of the more positive charge on the sulfur atom of the DMSO molecule, it has a strong polar interaction.…”
Section: Influence Of Dmsomentioning
confidence: 99%
“…Because of the structural complexities of proteins and the non-feasibility of direct thermodynamic studies, amino acids and oligopeptides are often used as model compounds since they are the fundamental components of proteins. (1)(2)(3) The partial molar volume is a characteristic parameter showing the interaction between molecules in solution. Most of the previous studies on amino acids and peptides have been restricted to water at a specified temperature (often at T = 298.15 K).…”
Section: Introductionmentioning
confidence: 99%
“…for LT and LPT, respectively [12,13]. Thermal effusivity (e) is the ability to exchange heat with the environment by the material and is given as [14]:…”
Section: Characterizationmentioning
confidence: 99%